An economic analysis of the impact of removing organic waste from small scale cage aquaculture systems in irrigation dams in the Western Cape - Gumbo, Tichaona (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Agricultural Economics))--University of Stellenbosch, 2011.